0 голосов
91 просмотров

Составьте сумму и разность выражений m+0,1n и 2(m-0,3) и упростите их.

(15 баллов) 1 по предмету Алгебра

1 Ответ

0 голосов
 
Лучший ответ

(m+0,1n)+(2(m-0,3))=

m+0,1n+2m-0,6=3m+0,1n-0,6

 

(m+0,1n)-(2(m-0,3))=

m+0,1n-2m+0,6=-m+0,1n+0,6

 

Начинающий (924 баллов) 1 2

Похожие вопросы

0 голосов
1 ответ 1 просмотр
0 голосов
1 ответ 0 просмотров
0 голосов
1 ответ 0 просмотров
0 голосов
1 ответ 1 просмотр
0 голосов
1 ответ 0 просмотров
0 голосов
1 ответ 0 просмотров
0 голосов
1 ответ 0 просмотров
...